Choose Good Food! : My Eating Tips - Bellisario, Gina; Conger, Holli (Minneapolis, MN : Millbrook Press, 2014)
A picky eater learns about healthy food choices, visits the supermarket, and prepares a delicious snack.
Picky eater -- Five food groups -- Energy lunch.
Includes bibliographical references (page 24) and index.
Keywords: Nutrition -- Juvenile literature; Food habits -- Juvenile literature; Lunchbox cooking -- Juvenile literature; Nutrition; Food habits; Lunchbox cooking